The Quarrel Between Poetry and Philosophy : Perspectives Across the Humanities - Burns, John (Routledge Focus on Literature Ser, 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Permissions -- Acknowledgments -- Introduction -- 1 Origins of the Quarrel -- 2 Vergil and Broch in Worlds Upside Down: Living the Quarrel Between Poetry and Philosophy -- 3 Lessons, Lies, and Legacies: The Place of Poetry in Thomas More's Utopia and Philip Sidney's Defense of Poesy -- 4 La Malinche and the Noble Lie -- 5 Making and Discovering in Shakespeare's Sonnets -- 6 Vergil, Broch, and a "Place" for Art: Answering the Quarrel -- 7 Jorge Pimentel: Obfuscation for Clarity's Sake -- 8 Turning With Heidegger Towards Poetry -- Coda -- Index.